If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + -5x = 8 + -8x Solving -4 + -5x = 8 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. -4 + -5x + 8x = 8 + -8x + 8x Combine like terms: -5x + 8x = 3x -4 + 3x = 8 + -8x + 8x Combine like terms: -8x + 8x = 0 -4 + 3x = 8 + 0 -4 + 3x = 8 Add '4' to each side of the equation. -4 + 4 + 3x = 8 + 4 Combine like terms: -4 + 4 = 0 0 + 3x = 8 + 4 3x = 8 + 4 Combine like terms: 8 + 4 = 12 3x = 12 Divide each side by '3'. x = 4 Simplifying x = 4
| 8(t-2)+6t=7(2t+2)-10 | | 6.3+.5x=16.3 | | 120-8-8-8= | | -[6x+(4x+3)]=7-(5x+6) | | 4.28-.4x=1.48 | | -2(4s-2)-4=-3(7s+5)-5 | | 2x+2=11-7x | | -3x+9=81+6x | | 5(a-3)=3(a+7) | | 4x+5=2x+17 | | 13y+5=3y+25 | | x-9=-15+7x | | -2(4s-2)=-3(7s+5)-5 | | 14t=2t+48 | | 6n+5=34 | | -20x+x^2=-16 | | C=85+0.5Yd | | 59+4141414141414141441= | | 6x+4=-(-25) | | 10.8-0.2x=9whatisx | | Y=105+0.375Y+75+60+10 | | (2(x-2)-4)(3x(2x-8))=0 | | 10.8-.2x=9 | | 5x^2+8xy+5y^2=45 | | 4(a-3)=2(3-a) | | 2x+3=x-2 | | x+5x=180 | | 5(x-2)=5 | | 5x^2+2=0 | | x^2-15x=15 | | (x^2+2)(3x+2y)= | | (4xy+2x^2y)(2x^2-3xy)= |